Workplace Experiences of Persons with Disabilities - Connelly,Catherine; Baldridge,David (Human Relations, 2018)
Human Relations virtual special issue introduction: Workplace experiences of persons with disabilities Human Relations virtual special issues bring together and highlight related research on a particular topic. Each collection is compiled and introduced by one of the journal’s editors; here we have Catherine E Connelly alongside David Baldridge, Human Relations Editorial Board member and author on this topic. Readers can access our virtual special issue on Workplace experiences of persons with disabilities here: https://journals.sagepub.com/page/hum/collections/virtual-special-issues/persons-with-disabilities
Keywords: Management